Propuesta de mejoramiento del proceso de producción de fertilizantes granulados de la empresa Feragrocol S.A.S (2021)
This article resulted from a qualitative investigation carried out in the company Feragrocol SAS and its principal purpose is to make an improvement proposal for the granular fertilizer production process. The descriptive exploratory methodology used an inductive-descriptive method on two lines for fertilizers, Silix Foz and Sol Producción. As a result, the main problem is the inadequate management of resources during the production chain of granulated fertilizers, emphasizing areas like standardization of processes, plant distribution, and statistical quality control.